Using new artificial bee colony as probabilistic neural network for breast cancer data classification. Issue 2 (7th July 2021) - Shah, Habib
Abstract : Purpose: Breast cancer is an important medical disorder, which is not a single disease but a cluster more than 200 different serious medical complications. Design/methodology/approach: The new artificial bee colony (ABC) implementation has been applied to probabilistic neural network (PNN) for training and testing purpose to classify the breast cancer data set. Findings: The new ABC algorithm along with PNN has been successfully applied to breast cancers data set for prediction purpose with minimum iteration consuming. Originality/value: The new implementation of ABC along PNN can be easily applied to times series problems for accurate prediction or classification.